Implementasi Fuzzy Model Tahani Untuk Perancangan Sistem Pendukung Keputusan Penerimaan Taruna Baru - Hidayat, Eko Hidayat (Universitas Diponegoro, 2015)
In this research, a decision support system design had been done by using Fuzzy database of Tahani Model, to know the excess of Fuzzy Tahani Model in a support system design of new cadets’ admission decision. The designed system was by the sequence of data input Fuzzy or non Fuzzy, the representation of membership function on each variable input Fuzzy, the process of Fuzzification on each variable into each Fuzzy set, the use of Zadeh basic operator to operate the Fuzzy set until give a recommendation. The result showed that the built system could give recommendation to support the decision of selected cadets based on the input criteria given. The excess of this system was on the flexibility of giving recommendation. The compatability of accepted cadets’ candidate with the recommendation of given system was 66.96%, due to the management strategis interest. Keywords : Fuzzy Database; New Cadet’s Admission; Decision Support Systems